2016
DOI: 10.1007/s00405-016-3910-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a canalplasty and a canal wall reconstruction on perceived sound quality: preliminary results

Abstract: Objective of this work was to evaluate the perceptual effect of the acoustic properties before and after canalplasty and a reconstruction of the posterior canal wall in revision modified radical cavity surgery. This is a prospective study. Twenty normal hearing subjects were presented six simulated sound conditions representing the acoustic properties of six different ear canals (two normal ears, and two pre- and postoperative conditions). The six different real ear unaided responses of these ear canals were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…Gantz et al postulated that these marginal hearing outcomes were due to ongoing Eustachian tube dysfunction and tympanosclerosis. We agree with this assessment and would add that CWR technique may also alter the acoustic properties of the ear and/or the vibratory capacity of the ossicular chain …”
Section: Discussionsupporting
confidence: 76%
“…Gantz et al postulated that these marginal hearing outcomes were due to ongoing Eustachian tube dysfunction and tympanosclerosis. We agree with this assessment and would add that CWR technique may also alter the acoustic properties of the ear and/or the vibratory capacity of the ossicular chain …”
Section: Discussionsupporting
confidence: 76%
“…Even less extensive surgical alterations of the OEAC, such as an osseous canalplasty, lead to changes in ear canal acoustics [9]. These observations seem to indicate that volume changes of the ear canal lead to alterations in ear canal acoustics [8,9]. In previous studies, we have demonstrated that these surgical alterations of the OEAC provoke an altered perception of the sound [8,9].…”
Section: Introductionmentioning
confidence: 73%
“…Due to its anatomical dimensions the external auditory ear canal acts as a filter to reduce low frequencies and enhance mid to high frequencies [3]. Surgical modification of the osseous external auditory canal (OEAC) changes the acoustic properties of the external ear canal [4][5][6][7][8][9]. For example, in case of a cavity condition, the acoustic properties shift towards an amplification of the soundwaves of low to mid frequencies and an reduction in soundwaves of high frequencies [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations